Profile of Patients Neutropenia Fever Unrelated to Chemotherapy in Dr. Cipto Mangunkusumo General Hospital - Danasasmita, Gantira; Chen, Lie Khie; Sinto, Robert; Nugroho, Pringgodigdo (Jurnal Penyakit Dalam Indonesia, 2020)
Introduction. The condition of neutropenia increases the risk of infection. The causes of neutropenia are widely discussed as side effects of chemotherapy, but patients with neutropenia who are not due to side effects of chemotherapy are increasing in number. This study aims to provide an overview of the characteristics of neutropenic fever population unrelated to chemotherapy. Method. The study was conducted retrospectively on the medical records of neutropenic fever patients who were not chemotherapy-related in the National Hospital Dr. Cipto Mangunkusumo in January 2018-November 2019. Variables studied included demographic, clinical characteristics, classification of multinational association of supportive care in cancer (MASCC) scores and their etiology, and mortality outcomes within 5 days of treatment. Results. Total of 68 subjects were included in this study, consist of 50% female and 50% male with median age was 38.5 years (interquartile range 27). Diagnosis data showed that 86.8% subjects were patients with hematological abnormalities, 3 patients had solid tumors (lymphoma, colon cancer and lung cancer), and the rest were non-malignant diseases. Analysis showed that 72.1% onset of fever was found in outpatient care, the rest was inpatient care. The mean value of absolute neutrophil count was 201.50 (SD 173.18), meanwhile the mean MASCC score was 21 (SD 4.54) in the low-risk category. A total of 35 subjects (51.5%) had a MASCC low risk score and 33 subjects (48.5%) had a high risk. The median procalcitonin subject was 1.99 ng / mL (range 0.11 - 178.30). The 5-days mortality incidence was 54.4%. Chi-square analysis of the two groups found significant differences in care mortality (p <0.05). Analysis with Independent T-test also showed a significant differences in the parameters of age and systolic blood pressure values between the high risk and low risk groups. Conclusions. The majority etiologies among subjects were haematological disorders. Based on the MASCC score, most of the subjects were in the high-risk group. Total of mortality incidence was 54.4%.